Predictive Value of Various Risk Factors for Preterm Labor - Purvi K Patel; Dipa S Pitre; Suman P Bhooker (Medsci Publications, 2015)
Objective: The objectives of this study were to study the various etiological factors responsible for onset of preterm labor and to evaluate the predictive value of these risk factors for spontaneous preterm labor. Methods: This prospective comparative study was conducted over a period of 1 year and included 240 women; of which 120 in preterm labor were enrolled in the study group and 120 with term pregnancy in labor were enrolled in the control group. History, clinical examination and investigations were carried out and risk factors for preterm labor were noted and analyzed to find out the predictive value of the risk factors for preterm labor. Results: Maximum numbers of patients (31.6%) were in the 35-36 weeks gestational age group. When both the groups were compared as regards risk factors, the cases showed a high incidence of infections; 21.7% incidence of chorioamnionitis, 32.5% incidence of bacterial vaginosis and a 12.5% incidence of urinary tract infections. Prior second trimester abortion was found in 13.3% cases and a history of prior preterm birth was found in 15% cases. Uterine over distension was observed in 20.83% cases. Maternal medical disorders were present in 60% cases. Conclusions: Multiple pregnancy, Prior preterm birth, Infections, Prior second trimester abortions and medical disorders in mother are strongly associated with an increased risk of preterm labor.